Continuous professional development programmes for school principals in the 21st century: Lessons learned from educational leadership practices - Faizuddin, Ahmad; Azizan, Noor Azlinna; Othman, Azam; Ismail, Siti Noor (Frontiers in Education, 2022)
Continuous professional development (CPD) is important for educational leaders to improve institutional performance and students’ learning outcomes. Yet, organizing effective professional development programmes are often more complex than we might assume. The current study aims to explore the challenges of managing CPD for high school principals in Indonesia. Six high school principals and three officers of the Ministry of Education and Cultures (MoEC) were interviewed. Qualitative data from the interviews were analysed and coded thematically using Atlas.ti. Several themes and main points emerged from the transcripts of interviews. The findings revealed some challenges in managing CPD programmes at schools. They include resistance to change, technicality and workload, almost zero follow-ups, unprofessional recruitment, and unclear training syllabus. Among the suggestions to improve the CPD programmes are building personal approaches, developing professional skills, establishing a professional recruitment system, making continuous training programmes, and optimizing school organizations. This study can be used as an additional guide to implement effective CPD and can be a platform to improve the professional development of educational leaders.